Analysis of reporting completeness in exercise cancer trials: a systematic review (2019)
ABSTRACT: Background: Exercise is an effective therapeutic intervention for cancer survivors. Concerns about the completeness of reporting of exercise interventions have been raised in the literature, but without any formal analysis. This study aimed to evaluate the completeness of reporting of exercise interventions for cancer survivors in a large sample of randomized clinical trials (RCTs). Methods: We developed a pre-defined protocol. We searched MEDLINE, EMBASE, and CENTRAL for exercise trials in oncology between 2010 and 2017. Pairs of independent researchers screened the records, extracted study characteristics, and assessed 16 items on the TIDieR checklist (i.e., the 12 items, with item 5 divided into two and item 8 divided into four). For each of these items, the percentage of interventions in the included studies that reported the item was calculated. Results: We included 131 RCTs reporting 138 interventions in the analysis. Breast cancer was the most common type of cancer (69, 50%), and aerobic exercise was the most studied exercise modality (43, 30%) followed by combined aerobic and resistance training (40, 28%). Completeness of reporting ranged from 42 to 96% among the TIDieR items; none of the items was fully reported. ‘Intervention length’ was the most reported item across interventions (133, 96%), followed by ‘rationale’ (131, 95%), whereas ‘provider’ (58, 42%) and ‘how well (planned)’ (63, 46%) were the two least reported items. Half of the TIDieR items were completely reported in 50 to 70% of the interventions, and only four items were reported in more than 80% of the interventions (Items 2 and 8a to c). The seven items deemed to be core for replication (Items 3 to 9) exhibited a mean reporting of 71%, ranging from 42 to 96%. Conclusion: Exercise training interventions for cancer survivors are incompletely reported across RCTs published between 2010 and 2017. The reporting of information about the provider, materials, and modifications require urgent improvements. Stronger reporting will enhance usability of trial reports by both healthcare providers and survivors, and will help to reduce research waste.